Digital Music Industry – Background Synthesis - Derek Sellin; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2017)
After 15 years of decline, music industry revenues appear finally to have turned a corner with the growth of paid streaming services. However, the industry as a whole may not be equipped to handle the changes brought on by new technology: with affordable home recording equipment, independent artists can release music directly to online platforms; with streaming services, massive per-play consumption reports are generated daily; and with low artist payments reflecting consumer expectations that music should be free, there is growing pressure for the industry to be more transparent with royalty calculations and faster with their payments. In this paper, we describe the state of the global music industry today, and present historical and systemic factors which have led to the industry's lack of transparency and complexity. We summarize the primary copyrights and licenses involved in music, and present a simplified value web as a basis for future research into possible global solutions. We identify three process layers for infrastructure related to managing assets, rights, reporting, and payments, regardless of physical format: (1) rights ownership, (2) consumption data, and (3) payment systems. Focusing on rights ownership, we summarize the major issues with today's infrastructure, metadata, and protocols, highlighting causes for industry “black boxes,” the blockages in the system causing creators' royalty payments to get stuck in the system. Finally, we look at past collaborative initiatives, primarily the Global Repertoire Database (GRD), in order to gain key learnings, and we acknowledge nascent blockchain-related efforts. With the digital music industry thus synthesized, we outline further research to arrive at a future industry architecture and to understand the impacts of the likely music supply chain transformation, and the related managerial implications.
Keywords: 330; Digital platforms; Music industry; Value web; Global rights database; Black boxes; Metadata; Blockchain